Development of Career Skills Model Based on Sufficiency Economy Philosophy Toward BCG Economy Model for Youth - Jitbantao, Tongrak; Prasunin, Jamaree; Treeaekanukul , Lelar; Muangjai , Tippawan; Na Phikun, Praphat (Community and Social Development Journal, 2025)
The purpose of the project were to establish a career skills model for young entrepreneurs based on the sufficiency economy concept toward business and community development (BCG) and to study the career skills based on the sufficiency economy philosophy towards BCG of young entrepreneurs. In order to investigate the career skills of young entrepreneurs in Chiang Rai and provide recommendations for career skill development based on the sufficiency economy ideology toward BCG Economy Model for youth entrepreneurs, a focus group methodology including 160 key informants was employed in the qualitative research method. Additionally, 400 participants in the quantitative study approach employing the professional skills exam for adolescent entrepreneurs were used. The findings of the research showed that young people had a high degree of confidence in themselves. They were fast to self-discover and determined. They might modify technology to suit their needs. Learning and inventive, informational, life and career, problem-solving, creative thinking, and emotional regulation abilities were today's vital life and professional skills. The integration of professional skills upgrading with the sufficiency economy ideology is a recognized strategy for sustainable business among youth entrepreneurs. It is based on two requirements: knowledge and virtue, honesty, responsibility, and transparency; and three principles: moderation, rationality, and immunity. Ultimately, it points toward the BCG (Bio Economy, Circular Economy, and Green Economy).